Composite membrane as well as preparation method and application thereof
By constructing a composite membrane structure in the interfacial evaporator, the problems of insufficient hydrophilicity and pollution inhibition were solved, the evaporation efficiency and flux were improved, the environmental burden was reduced, and efficient seawater desalination and saline wastewater treatment were achieved.
Patent Information
- Application Number
- CN202511754095.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-26
- Publication Date
- 2026-02-10
- Estimated Expiration
- 2045-11-26
AI Technical Summary
Existing interfacial evaporators suffer from problems such as insufficient hydrophilicity, discontinuous water supply, long start-up time, salt crystallization blockage, difficulty in controlling organic pollution, reduced flux, and heavy environmental burden. Furthermore, the high cost and difficulty in recycling of photothermal materials hinder large-scale applications.
A composite membrane structure is adopted, including a base membrane, a functional layer and a photothermal layer. The functional layer is formed by alternating deposition of cationic polyelectrolyte layers and anionic polyelectrolyte layers, and the photothermal layer is composed of carbon nanotubes or molybdenum disulfide-supported carbon nanotubes. Through layer-by-layer self-assembly technology and stabilization treatment, a hydrophilic, antibacterial and broad-spectrum absorption composite membrane is constructed.
It improves evaporation efficiency, reduces apparent enthalpy of vaporization, inhibits biofouling, maintains good flux and durability, reduces environmental burden, and achieves efficient seawater desalination and saline wastewater treatment.
Smart Images

Figure CN121490593A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer functional membrane materials technology, and in particular to a composite membrane, its preparation method and application. Background Technology
[0002] Seawater desalination plays a crucial role in water resource management and ecological security. The emerging solar-powered interfacial evaporation technology, relying on in-situ light-to-heat conversion and short-range vaporization mass transfer near the liquid surface, theoretically reduces system energy consumption and equipment complexity, and is considered a potential pathway for distributed desalination and polluted water purification. However, existing interfacial evaporators still face a series of common bottlenecks restricting their engineering applications: First, insufficient hydrophilicity and hydration layer at the evaporation interface lead to discontinuous water supply, long start-up times, and high apparent enthalpy of vaporization. Under high salinity conditions, salt crystals easily precipitate on the surface and flow back into the pores, causing blockage of mass transfer channels and efficiency fluctuations. Second, organic pollution and biofilm adhesion are difficult to suppress during long-term operation. Commonly used surface hydrophilization methods (such as introducing hydroxyl / ether bonds) have limited effectiveness in inhibiting protein adsorption and biofilm formation, and cleaning and disinfection accelerate material aging. Third, the pursuit of high absorption rates often involves high-dose deposition of photothermal particles or their bonding with resin, resulting in a dense coating layer that increases interfacial thermal and water resistance, leading to decreased flux, slower thermal response, and the risk of interlayer delamination. Furthermore, common support / evaporator materials such as polyacrylamide hydrogels and polyurethane foams are difficult to degrade, resulting in a heavy environmental burden after disposal. Additionally, the high cost and difficulty in recycling of some photothermal materials also negatively impact the life-cycle cost and sustainability of large-scale applications. Summary of the Invention
[0003] The main objective of this invention is to propose a composite membrane, its preparation method, and its application. The composite membrane is applied to solar interfacial evaporation and has high hydrophilicity, good antibacterial properties, and broad-spectrum absorption characteristics. It can reduce the apparent enthalpy of evaporation, improve evaporation efficiency, and maintain good flux and durability under interfacial evaporation conditions.
[0004] To achieve the above objectives, the present invention proposes a composite membrane comprising a base membrane, a functional layer, and a photothermal layer. The functional layer is disposed between the base membrane and the photothermal layer. The functional layer is formed by alternating deposition of a cationic polyelectrolyte layer and an anionic polyelectrolyte layer on the surface of the base membrane. The cationic polyelectrolyte layer includes an amphiphilic chitosan derivative layer.
[0005] In one embodiment, the anionic polyelectrolyte layer comprises a polyacrylic acid layer; and / or, Based on the total mass of the functional layers, the chitosan constitutes 0.5% to 2% of the total mass; and / or, The base film is made of polyaryletherketone, which has hydrophilic groups; and / or, The thickness of the base film is 1mm to 3mm; and / or, The thickness of the functional layer is 10nm~100nm; and / or, The thickness of the photothermal layer is 0.1mm to 0.3mm.
[0006] In one embodiment, the photothermal layer comprises a photothermal material, wherein: The photothermal material includes at least one of carbon nanotubes and molybdenum disulfide-supported carbon nanotubes; and / or, Based on the total mass of the composite film, the mass percentage of the photothermal material is 0.05% to 5%.
[0007] The present invention also proposes a method for preparing the composite membrane as described above, comprising the following steps: Preparation of base film; The base film is sequentially and alternately immersed in cationic polyelectrolyte solution and anionic polyelectrolyte solution for self-assembly and a single stabilization treatment to prepare a functional layer on the surface of the base film; A photothermal layer is deposited on the surface of the functional layer to obtain a composite film; The cationic polyelectrolyte solution includes an amphiphilic chitosan derivative solution.
[0008] In one embodiment, the amphiphilic chitosan derivative solution contains 0.3% to 1% by mass of the amphiphilic chitosan derivative; and / or, The anionic polyelectrolyte solution includes a polyacrylic acid solution, wherein the mass percentage of polyacrylic acid in the polyacrylic acid solution is 0.05% to 0.2%.
[0009] In one embodiment, the primary stabilization treatment is to treat the self-assembled base film with a stabilization solution, wherein: The stable solution comprises at least one of ethyltris(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide; and / or, The molar concentration of the stabilized solution is 1–50 mmol / L; and / or, The stabilization treatment time is 5 to 30 minutes.
[0010] In one embodiment, the step of fabricating a photothermal layer on the surface of the functional layer includes: The photothermal material is mixed with a dispersing solvent to obtain a photothermal material dispersion. The photothermal material dispersion is coated onto the surface of the functional layer at least twice, followed by a second stabilization treatment, to deposit a photothermal layer on the surface of the functional layer and obtain a composite film.
[0011] In one embodiment, the dispersion solvent comprises water and an organic solvent, the organic solvent comprising at least one of ethanol and isopropanol; and / or, The duration of the secondary stabilization treatment is 5-10 minutes; and / or, The mass of photothermal material in the dispersion of photothermal material in a single coating is 10~20μg per square centimeter.
[0012] In one embodiment, the step of preparing the base film includes: The polyaryletherketone solution is mixed with additives to obtain a casting solution; The casting solution is coated into a film by a scraper, evaporated in an air section, and treated in a water bath to obtain a base film. The polyaryletherketone solution comprises polyaryletherketone and a solvent, wherein the polyaryletherketone has hydrophilic groups; in: The polyaryletherketone solution comprises polyaryletherketone and a solvent, the solvent comprising dimethylacetamide; and / or, The additive includes ethylene glycol monomethyl ether; and / or, In the casting solution, the additive accounts for 5% to 15% by mass; and / or, In the polyaryletherketone solution, the polyaryletherketone accounts for 14% to 20% by mass; and / or, The evaporation time of the air segment is 1~10s; and / or, The temperature of the water bath treatment is 22~28℃.
[0013] The present invention also proposes an application of the composite membrane described above in a solar interface evaporation purification device, which is used for seawater desalination and / or treatment of saline wastewater.
[0014] In the technical solution of this invention, a functional layer is constructed on the surface of a base film, consisting of an amphiphilic chitosan derivative layer and an anionic polyelectrolyte layer. On one hand, the amphiphilic chitosan derivative exhibits excellent antibacterial effects; on the other hand, the amphiphilic chitosan derivative contains numerous hydrophilic groups such as hydroxyl groups, which reduces the energy required for water to escape from a liquid to a gaseous state, thereby lowering the enthalpy of evaporation. Furthermore, the aforementioned functional layer can form a hydration film in water, exhibiting superoleophobic properties, thus inhibiting contamination from organic dyes and other pollutants. It also heats up rapidly under light, providing even better antibacterial effects. The photothermal layer converts light energy into heat energy, promoting water evaporation and escape. Therefore, the composite film provided by this invention can reduce the apparent enthalpy of evaporation during interfacial evaporation and improve evaporation efficiency. Attached Figure Description
[0015] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on the structures shown in these drawings without creative effort.
[0016] Figure 1 The XRD pattern of the photothermal conversion material prepared in Example 2; Figure 2 This is a scanning electron microscope image of Example 2; Figure 3 These are contact angle test diagrams for Examples 1 and 2; Figure 4 The integrating sphere absorption spectra of Examples 1 and 2 are shown below; Figure 5 Infrared thermal images of Examples 1 and 2; Figure 6 Heat flow-temperature curves for seawater and seawater treated with the composite membrane prepared in Example 2.
[0017] The realization of the objective, functional features and advantages of the present invention will be further explained in conjunction with the embodiments and with reference to the accompanying drawings. Detailed Implementation
[0018] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0019] It should be noted that if the embodiments of the present invention involve directional indicators (such as up, down, left, right, front, back, etc.), the directional indicators are only used to explain the relative positional relationship and movement of the components in a specific posture. If the specific posture changes, the directional indicators will also change accordingly.
[0020] Furthermore, if the embodiments of this invention involve descriptions such as "first" or "second," these descriptions are for descriptive purposes only and should not be construed as indicating or implying their relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined with "first" or "second" may explicitly or implicitly include at least one of those features. Additionally, the use of "and / or" or "and / or" throughout the text includes three parallel solutions. For example, "A and / or B" includes solution A, solution B, or a solution where both A and B are satisfied simultaneously. Furthermore, the technical solutions of the various embodiments can be combined with each other, but this must be based on the ability of those skilled in the art to implement them. When the combination of technical solutions is contradictory or impossible to implement, it should be considered that such a combination of technical solutions does not exist and is not within the scope of protection claimed by this invention.
[0021] Existing interfacial evaporators still face a series of common bottlenecks restricting their engineering applications: First, insufficient hydrophilicity and hydration layer at the evaporation interface lead to discontinuous water supply, long start-up times, and high apparent enthalpy of vaporization. Under high salinity conditions, salt crystals easily precipitate on the surface and flow back into the pores, causing blockage of mass transfer channels and efficiency fluctuations. Second, organic pollution and biofilm adhesion are difficult to suppress during long-term operation. Commonly used surface hydrophilization methods (such as introducing hydroxyl / ether bonds) have limited effect on inhibiting protein adsorption and biofilm formation, and cleaning and disinfection accelerate material aging. Third, the high-dose deposition of photothermal particles or the use of resin bonding to pursue high absorption rates often results in a dense coating layer, increasing interfacial thermal and water resistance, leading to decreased flux, slower thermal response, and the risk of interlayer delamination. In addition, common support / evaporator materials such as polyacrylamide hydrogels and polyurethane foams are difficult to degrade, resulting in a heavy environmental burden after disposal; some photothermal materials are expensive and difficult to recycle, which is also detrimental to the life-cycle cost and sustainability of large-scale applications.
[0022] In view of this, the present invention proposes a composite membrane, the composite membrane comprising a base membrane, a functional layer and a photothermal layer, wherein the functional layer is disposed between the base membrane and the photothermal layer, and the functional layer is formed by alternating deposition of a cationic polyelectrolyte layer and an anionic polyelectrolyte layer on the surface of the base membrane, wherein the cationic polyelectrolyte layer comprises an amphiphilic chitosan derivative layer.
[0023] In some embodiments, the anionic polyelectrolyte layer includes a polyacrylic acid layer; the chitosan accounts for 0.5% to 2% of the total mass of the functional layers; the base membrane is made of polyaryletherketone, which has hydrophilic groups. The hydrophilic groups in the base membrane can further improve the hydrophilicity of the system and enhance its water transport capacity. The hydrophilic groups may, exemplarily, include hydroxyl groups.
[0024] In some embodiments, the thickness of the composite film is less than 4 mm, which can achieve better photothermal effects and a better evaporation rate.
[0025] In some embodiments, the thickness of the base film is 1 mm to 3 mm; the thickness of the functional layer is 10 nm to 100 nm; and the thickness of the photothermal layer is 0.1 mm to 0.3 mm.
[0026] In some embodiments, the photothermal layer includes a photothermal material, which includes at least one of carbon nanotubes and molybdenum disulfide-supported carbon nanotubes.
[0027] In some embodiments, the photothermal material includes carbon nanotubes (CNTs). Carbon nanotubes possess full-spectrum high absorption properties, enabling them to efficiently capture sunlight and convert it into heat energy. Simultaneously, their high thermal conductivity allows for rapid heat transfer to interfacial moisture, achieving rapid evaporation. Furthermore, their stable sp... 2 The hybrid carbon structure enables it to operate stably for extended periods in harsh environments, while its porous network structure provides channels for moisture transport and vapor escape. Therefore, the use of carbon nanotubes offers advantages such as broad-spectrum absorption, low heat capacity, and low water resistance, thereby increasing the evaporation rate.
[0028] In some embodiments, the photothermal material includes molybdenum disulfide-supported carbon nanotubes (MoS2@CNT), which have a wider and stronger spectral absorption characteristic in the near-infrared region, thereby further improving the interfacial vaporization rate and evaporation efficiency.
[0029] It should be noted that the molybdenum disulfide-supported carbon nanotubes can be obtained by purchase or prepared in-house. The preparation method for molybdenum disulfide-supported carbon nanotubes is as follows: carbon nanotubes are mixed with ammonium molybdate tetrahydrate and thioacetamide in water, and then heated in a microwave digestion vessel. The mixture is then washed alternately with water and anhydrous ethanol, and dried at 80°C. Furthermore, polyvinylpyrrolidone can be added during preparation to improve dispersion stability.
[0030] In some embodiments, the photothermal layer includes a photothermal material, and the mass percentage of the photothermal material is 0.05% to 5% of the total mass of the composite film. The composite film provided by the present invention can achieve high broadband absorption and low heat capacity rapid thermal response with a low amount of photothermal material (0.05% to 5%), while avoiding pore blockage, improving evaporation efficiency, and minimizing material and environmental burden.
[0031] The present invention also proposes a method for preparing the composite membrane as described above, comprising the following steps: Preparation of base film; The base film is sequentially and alternately immersed in cationic polyelectrolyte solution and anionic polyelectrolyte solution for self-assembly and a single stabilization treatment to prepare a functional layer on the surface of the base film; A photothermal layer is deposited on the surface of the functional layer to obtain a composite film; The cationic polyelectrolyte solution includes an amphiphilic chitosan derivative solution.
[0032] By employing a layer-by-layer self-assembly technique, the base membrane is alternately immersed in positively charged cationic polyelectrolyte solutions and negatively charged anionic polyelectrolyte solutions. Relying on electrostatic adsorption, the base membrane is alternately deposited on the membrane surface to form a molecular-level multilayer film. Finally, a stabilization treatment is performed to enhance its stability. This method can reduce the apparent enthalpy of evaporation at the evaporation interface and inhibit organic and biological pollution, thereby increasing the evaporation rate of the composite membrane.
[0033] In some embodiments, the amphiphilic chitosan derivative solution contains 0.3% to 1% by mass of the amphiphilic chitosan derivative, preferably 0.5% by mass. The anionic polyelectrolyte solution includes a polyacrylic acid solution, containing 0.05% to 0.2% by mass of the polyacrylic acid, preferably 0.1% by mass. The pH of the amphiphilic chitosan derivative solution is 5.0 to 6.5, and the pH of the polyacrylic acid solution is 5.5 to 6.5.
[0034] In some embodiments, the base film is sequentially and alternately immersed in cationic polyelectrolyte solution and anionic polyelectrolyte solution for layer-by-layer self-assembly cycles 1 to 2 times.
[0035] In some embodiments, the initial stabilization process involves treating the self-assembled base film with a stabilizing solution. This transforms the polyelectrolyte multilayer film, initially formed by electrostatic attraction, into a denser and more stable three-dimensional network structure with covalent bonds.
[0036] Further, the stabilizing solution comprises at least one of ethyltris(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide; the molar concentration of the stabilizing solution is 1-50 mmol / L, preferably 10 mmol / L. The duration of the single stabilization treatment is 5-30 min. The pH of the single stabilization treatment is 5.5-6.5.
[0037] Furthermore, the composite layer after initial stabilization is washed with deionized water. After stabilization, the composite layer is washed until the conductivity is below 50 microsiemens per centimeter.
[0038] In some embodiments, the amphiphilic chitosan derivative is an amphiphilic polymer obtained by activating and grafting L-isoleucine onto the chitosan quaternary ammonium salt backbone with ethyltris(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide.
[0039] In some embodiments, the step of fabricating a photothermal layer on the surface of the functional layer includes: The photothermal material is mixed with a dispersing solvent to obtain a photothermal material dispersion. The photothermal material dispersion is coated onto the surface of the functional layer at least twice, followed by a second stabilization treatment, to deposit a photothermal layer on the surface of the functional layer and obtain a composite film.
[0040] In some embodiments, the dispersion solvent comprises water and an organic solvent, wherein the organic solvent comprises at least one selected from ethanol and isopropanol. The volume ratio of water to organic solvent in the dispersion solvent is (3~7):3.
[0041] In some embodiments, the mass percentage of the photothermal material in the photothermal material dispersion is 0.01% to 0.05%.
[0042] In some implementations, the secondary stabilization process takes 5 to 10 minutes.
[0043] In some embodiments, the mass of photothermal material in a single coating of photothermal material dispersion is 10-20 μg per square centimeter. This can be accumulated to the target load through multiple coatings.
[0044] The secondary stabilization treatment involves treating the base film coated with the photothermal material using a second stabilizing solution. The second stabilizing solution comprises at least one of ethyltris(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide; the molar concentration of the second stabilizing solution is 1-50 mmol / L, preferably 5 mmol / L. The duration of the secondary stabilization treatment is 5-10 min.
[0045] In some embodiments, when the photothermal material dispersion is coated onto the surface of the functional layer at least twice, multiple coatings are performed by immersion spunbonding or spray spunbonding to ensure that the photothermal material loading reaches the target range.
[0046] It should be noted that the composite membrane after secondary stabilization is washed and then stored in a wet state.
[0047] In some embodiments, the polyaryletherketone is prepared by nucleophilic substitution polycondensation of hydroxyl-containing bisphenol A and difluorobenzophenone in dimethylacetamide with anhydrous potassium carbonate as an acid scavenger. The base membrane is an asymmetric porous base membrane, which is formed using a solvent-inducible phase separation method.
[0048] In some embodiments, the step of preparing the base film includes: The polyaryletherketone solution is mixed with additives to obtain a casting solution; The casting solution is coated into a film by scraping, evaporated in an air section, and treated in a water bath to obtain the base film.
[0049] The polyaryletherketone solution comprises polyaryletherketone and a solvent, wherein the polyaryletherketone has hydrophilic groups; in: The polyaryletherketone solution includes polyaryletherketone and a solvent, wherein the solvent includes dimethylacetamide; the additive includes ethylene glycol monomethyl ether; in the casting solution, the additive accounts for 5% to 15% by mass; in the polyaryletherketone solution, the polyaryletherketone accounts for 14% to 20% by mass; the evaporation time in the air section is 1 to 10 seconds; the temperature of the water bath treatment is 22 to 28°C. After the casting solution solidifies in the water bath treatment, it can be washed with water at 45 to 55°C to obtain the base film.
[0050] The composite membrane proposed in this invention has a surface static contact angle of no more than 30 degrees. When the composite membrane is subjected to an interfacial evaporation test in a 3.5% sodium chloride solution with a light intensity of about 1 kW per square meter, it exhibits a higher evaporation rate and a lower apparent enthalpy of evaporation compared to the base membrane.
[0051] The present invention also proposes an application of the composite membrane described above in a solar interface evaporation purification device, which is used for seawater desalination and / or treatment of saline wastewater.
[0052] In the technical solution of this invention, a stable hydrophilic porous polymer base membrane is used as the framework, and a chemically stable nanoscale hydrophilic-charged-antibacterial interface layer (functional layer) is constructed on its surface to reduce the apparent enthalpy of evaporation at the evaporation interface and inhibit organic and biological pollution. A thin and strong absorption layer is formed on the outermost layer with a low amount of uniformly dispersed photothermal material to take into account broad-spectrum absorption, low heat capacity and low water resistance, and minimize the burden on materials and the environment.
[0053] The technical solution of the present invention will be further described in detail below with reference to specific embodiments and accompanying drawings. It should be understood that the following embodiments are only used to explain the present invention and are not intended to limit the present invention.
[0054] Example 1 This embodiment provides a composite membrane, the preparation method of which includes the following steps: (1) Dissolve polyarylether ketone in dimethylacetamide and add ethylene glycol monomethyl ether. Stir mechanically at 60°C for about 10 hours until homogeneous and transparent. After filtration and degassing, a casting solution is obtained (the mass percentage of polyarylether ketone is 18%; the mass percentage of ethylene glycol monomethyl ether is 10%). The casting solution is coated onto a nonwoven fabric with a 190-micron doctor blade. The mixture is then evaporated in the air section for 3 seconds at 20°C and a relative humidity of about 40%. The mixture is then placed in a 25°C deionized water coagulation bath until the phase inversion is complete. Finally, it is washed thoroughly in 50°C hot water to obtain a base film, which is then stored in a wet state for later use. (2) The base film was sequentially impregnated with an amphiphilic chitosan derivative solution and a polyacrylic acid solution to form a nanoscale composite layer (amphiphilic chitosan concentration 0.5%, impregnation time 15 minutes; polyacrylic acid concentration 0.1%, impregnation time 5 minutes); two self-assembly cycles were repeated. Subsequently, under pH conditions of 5.5-6.5, it was stabilized once with ethyltris(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide for 10 minutes, with a stabilization solution concentration of 10 mmol / L; after thorough washing with water, the functional layer was obtained. (3) Carbon nanotubes were dispersed in a mixed medium of water and ethanol (the volume ratio of water to ethanol was 1:1) to obtain a carbon nanotube dispersion (the mass percentage of carbon nanotubes was 0.02%). After sonication for 15 minutes, impregnation and spin deposition were performed, and multiple thin coatings were used to make the total load of carbon nanotubes reach 0.5% of the dry weight of the composite membrane. Subsequently, the membrane was stabilized for 10 minutes with 5 mmol / L of monoethyltris(3-dimethylaminopropyl)carbodiimide hydrochloride and 5 mmol / L of N-hydroxysuccinimide. After washing with water, the composite membrane was obtained and stored in a wet state. The thickness of the composite membrane was 3 mm.
[0055] Example 2 This embodiment provides a composite membrane, except that molybdenum disulfide-supported carbon nanotubes are used instead of carbon nanotubes, and the other steps are the same as in Embodiment 1.
[0056] In Example 2, step (3) includes: dispersing molybdenum disulfide-loaded carbon nanotubes in a mixed medium of water and ethanol (the volume ratio of water to ethanol is 1:1) to obtain a molybdenum disulfide-loaded carbon nanotube dispersion (the mass percentage of molybdenum disulfide-loaded carbon nanotubes is 0.02%); after sonication for 15 minutes, impregnation and spin-coating deposition are performed, and multiple thin coatings are used to make the total loading mass of molybdenum disulfide-loaded carbon nanotubes reach 0.5% of the dry weight of the composite membrane; then, a second stabilization is performed for 10 minutes with 5 mmol / L of monoethyltris(3-dimethylaminopropyl)carbodiimide hydrochloride and 5 mmol / L of N-hydroxysuccinimide, followed by water washing to obtain the composite membrane, which is then stored in a humid state.
[0057] Molybdenum disulfide-supported carbon nanotubes are prepared through the following steps: 0.1 g of carbon nanotubes were ultrasonically dispersed in 20 mL of ultrapure water; 0.15 g of ammonium molybdate tetrahydrate was added and stirred to dissolve, followed by 0.5 g of thioacetamide and stirring to dissolve again; the solution was transferred to a polytetrafluoroethylene-lined microwave digestion vessel and microwaved for 3 minutes under ventilation (two 3-minute intervals can be used to enhance phase stability); after the reaction, solid-liquid separation was performed, and the solution was washed at least twice with deionized water and at least twice with anhydrous ethanol; the solution was dried at 80 °C to obtain powdered molybdenum disulfide-supported carbon nanotubes.
[0058] Comparative Example 1 Carbon nanotubes were refluxed at 90°C for 3 hours using a 3:1 mixture of concentrated H₂SO₄ and HNO₃, centrifuged until neutral, dried, and then ultrasonically dispersed to obtain a 0.5 wt% aqueous solution of carbon nanotubes. Chitosan was dissolved in 1.5 wt% dilute acetic acid and stirred for 3 hours until completely dissolved. After filtration to remove impurities, a 3 wt% chitosan solution was obtained. The carbon nanotube dispersion was slowly added dropwise to the chitosan solution, stirred for 2 hours, ultrasonicated for 45 minutes (400 W), and allowed to stand to remove bubbles, resulting in a mixed solution. The mixed solution was poured onto a PTFE plate, ventilated at room temperature for 4 hours, then vacuum dried at 50°C for 8 hours. After crosslinking in a 3 wt% glutaraldehyde solution for 2 hours, it was washed with water and dried to obtain a CNT / CS composite membrane (evaporator).
[0059] Performance testing (1) X-ray diffraction experiments were conducted on the molybdenum disulfide-supported carbon nanotubes prepared in Example 2, and the results are as follows: Figure 1 As shown. Figure 1 middle, Figure 1 The XRD pattern of the photothermal conversion material (molybdenum disulfide supported carbon nanotubes) prepared in Example 2 is shown. The sample shows a strong peak at 2θ≈26.0°, corresponding to the (002) interlayer diffraction of CNTs, indicating that the support maintains a good graphitization structure. Weak but distinguishable diffraction peaks or shoulder peaks appear at 32.6~32.9°, 36.0~36.4°, 39.3~39.7°, 58.1~58.5° and 60.0~60.4°, which are consistent with the (100), (101), (103), (110) and (112) positions of the MoS2 standard card. At the same time, the typical MoS2 (002) interlayer peak near 14.4° is significantly weakened and broadened, indicating that the generated MoS2 is loaded in a few-layer / nanocrystalline morphology and has certain stacking defects. No characteristic peaks matching MoO3 or MoO2 were observed, indicating that the sample is dominated by MoS2 and has good phase purity. In summary, this method has generated and stably loaded MoS2 nanocrystals in situ on the CNT surface, providing a direct structural basis for the high light absorption and low thermal resistance of the photothermal layer, which is consistent with the performance improvements such as increased integral absorption rate and reduced apparent enthalpy of vaporization in the examples.
[0060] (2) The composite film prepared in Example 2 was tested using a scanning electron microscope, and the scanning electron microscope image is shown below. Figure 2 As shown. By Figure 2 (Cross-sectional view, scale bar 500 μm, magnification 20x, secondary electron imaging, beam current 100 picoamperes, accelerating voltage 15 keV) It can be seen that the composite membrane (evaporator) substrate of this embodiment exhibits an open, interconnected, cellular porous network. The pore size is mainly distributed in the range of tens to hundreds of micrometers, with larger channel pores visible locally. The pore walls are composed of thin-plate ribs and bridging structures, with no obvious collapse or closure observed. This morphology conforms to the "honeycomb-finger" composite pore structure characteristics formed during solvent-induced phase separation, characterized by the coexistence of interconnected macropore-mesopore channels and relatively thin pore walls. This structure, on the one hand, facilitates rapid water absorption and steam discharge, reducing gas phase transport resistance; on the other hand, it reduces the effective volumetric heat capacity and heat conduction path, thereby reducing bulk heat loss, while providing sufficient mechanical support to prevent structural collapse under wet conditions. Combining the absorption of the integrating sphere and the heating results of thermal imaging, the cross-sectional morphology proves that the structure can achieve efficient light-heat-mass coupling transport under the condition of low density of the photothermal layer, providing direct morphological evidence for improving the evaporation rate and energy utilization efficiency.
[0061] (3) The composite films from Examples 1 and 2 were subjected to contact angle tests, such as... Figure 3 As shown, under the same test settings (same lens, needle height, and droplet rate), both Example 1 (photothermal layer is carbon nanotube) and Example 2 (photothermal layer is molybdenum disulfide supported carbon nanotube) exhibited instantaneous spreading and rapid absorption after the addition of deionized water: the droplets collapsed rapidly after landing and became invisible within 1 second, exhibiting superhydrophilic behavior with a contact angle approaching 0 degrees. This result indicates that the surface of the composite film (evaporator) and its near-surface layer have high surface energy and continuous capillary channels, enabling rapid water replenishment even in a dry state, thus ensuring the establishment of a stable liquid-gas interface in the early stages of light irradiation. This, along with the "open and interconnected porous structure" (scanning electron microscopy) and the "hydrophilic modification of the amphoteric chitosan / polyacrylic acid composite layer," corroborates the technical effect of this invention, achieving a high evaporation rate and good resistance to salt crystallization even under low photothermal layer density conditions.
[0062] (4) The photothermal materials in Examples 1 and 2 were tested using an integrating sphere ultraviolet-visible-near-infrared spectrophotometer, such as... Figure 4As shown, the absorption-wavelength curves of the two photothermal materials in the 250–2500 nm range indicate that Example 1 (carbon nanotubes) exhibits a broad peak near approximately 900–1000 nm, followed by a significant attenuation in the near-infrared long-wavelength band. Example 2 (molybdenum disulfide-supported carbon nanotubes) shows a continuous increase in absorption with increasing wavelength, exceeding that of Example 1 across the entire visible to near-infrared spectral range, with a particularly significant difference in the 900–2500 nm range. This spectral pattern suggests that the introduction of molybdenum disulfide effectively broadens the spectral response and enhances the ability to capture near-infrared energy from sunlight, possibly related to the band transitions and multiple scattering / reflection effects of layered molybdenum disulfide. This absorption advantage is consistent with the higher surface temperature observed in the thermal imaging results at 1 min, indicating that under the same irradiation, this photothermal layer is more likely to achieve a higher effective surface temperature and reduce interfacial heat loss, thereby improving the evaporation rate and energy utilization efficiency.
[0063] (5) The composite films in Examples 1 and 2 were scanned using an infrared thermal imager to obtain infrared thermal images as follows: Figure 5 As shown, the left figure is Example 1, and the right figure is Example 2. Under the same irradiation conditions (approximately 1 kW·m), -2 Under the same field of view and emissivity setting (ε=0.93), when using CNTs as the photothermal layer, the surface center temperature was approximately 78.5℃ after 1 min (ambient temperature 29℃), corresponding to ΔT≈49.5℃. After using MoS2-loaded CNTs, the temperature was approximately 84.8℃ after 1 min, corresponding to ΔT≈55.8℃, an increase of approximately 6.3℃ (≈12–13%) compared to CNTs. This temperature increase indicates that MoS2@CNTs have a wider / stronger absorption range in the visible-near infrared region, and achieve lower surface thermal resistance and faster initial heating through covalent anchoring with the amphoteric chitosan / polyacrylic acid composite layer; both contribute to a higher effective surface temperature, which is beneficial for improving the interfacial vaporization rate. This thermal imaging evidence is consistent with the MoS2 nanocrystal loading confirmed by XRD.
[0064] (6) The composite membrane obtained in Example 2 was tested using a differential calorimeter, and the temperature-heat flow curve was obtained as follows: Figure 6 As shown, the apparent enthalpy of vaporization in Example 2 is 1721 J / g, while the apparent enthalpy of vaporization in seawater is 2345 J / g. (From...) Figure 6As can be seen, compared with the seawater control, the seawater treated with the composite membrane of Example 2 exhibits a significantly reduced endothermic valley area and an earlier termination temperature zone, with an apparent enthalpy of vaporization reduced by approximately 26.6% compared to seawater. The significant decrease in endothermic demand indicates that the evaporator interface can drive vaporization with a lower heat load under the same illumination. This is generally attributed to the rearrangement of near-interfacial water molecules in the amphoteric chitosan / polyacrylic acid composite layer (increased proportion of free and intermediate water, decreased proportion of bound water) and the shortened heat and mass transfer paths resulting from the open and interconnected porous channels. This result is consistent with the phenomenon of enhanced absorption and higher thermal image temperature rise in the integrating sphere, jointly demonstrating that the present invention can achieve higher vaporization flux and energy utilization efficiency under a single solar radiation intensity.
[0065] The evaporation rate of the composite membranes prepared in Examples 1 and 2 was tested, and the composite membranes were used for seawater desalination. The concentration of metal ions after treatment was tested, and the results are recorded in Table 1.
[0066] The testing method is as follows: The composite film was placed on a polyurethane (PU) sponge with surface grooves (grooves measuring 4.0 × 4.0 × 0.2 cm). 3 The membrane was placed on top of the evaporator and then into a beaker containing 500 ml of seawater (3.5 wt% NaCl). A PU sponge was used to maintain the composite membrane (evaporator) semi-floating on the water surface. The membrane (evaporator) was irradiated using a simulator with a solar intensity of 1. The weight change of water evaporation was measured using an electronic analytical balance with an accuracy of 0.1 mg. The water evaporation rate was determined over 1 hour under steady-state conditions. The concentrations of sodium, potassium, magnesium, and calcium ions in the seawater after evaporation were also measured.
[0067] Table 1. Evaporation rates and metal ion concentrations of Examples 1 and 2, Comparative Example 1, and seawater.
[0068] As can be seen from Table 1, the salt removal rate of water after desalination treatment according to the present invention reaches 99.9%.
[0069] The above description is merely an exemplary embodiment of the present invention and does not limit the patent scope of the present invention. Any equivalent structural transformations made using the contents of the present invention specification and drawings under the technical concept of the present invention, or direct / indirect applications in other related technical fields, are included within the patent protection scope of the present invention.
Claims
1. A composite membrane, characterized in that, The composite membrane includes a base membrane, a functional layer, and a photothermal layer. The functional layer is disposed between the base membrane and the photothermal layer. The functional layer is formed by alternating deposition of a cationic polyelectrolyte layer and an anionic polyelectrolyte layer on the surface of the base membrane. The cationic polyelectrolyte layer includes an amphiphilic chitosan derivative layer.
2. The composite membrane as described in claim 1, characterized in that, The anionic polyelectrolyte layer includes a polyacrylic acid layer; and / or, Based on the total mass of the functional layers, the chitosan constitutes 0.5% to 2% of the total mass; and / or, The base film is made of polyaryletherketone, which has hydrophilic groups; and / or, The thickness of the base film is 1mm to 3mm; and / or, The thickness of the functional layer is 10nm~100nm; and / or, The thickness of the photothermal layer is 0.1mm to 0.3mm.
3. The composite membrane as described in claim 1, characterized in that, The photothermal layer comprises a photothermal material, wherein: The photothermal material includes at least one of carbon nanotubes and molybdenum disulfide-supported carbon nanotubes; and / or, Based on the total mass of the composite film, the mass percentage of the photothermal material is 0.05% to 5%.
4. A method for preparing a composite membrane as described in any one of claims 1 to 3, characterized in that, Includes the following steps: Preparation of base film; The base film is sequentially and alternately immersed in cationic polyelectrolyte solution and anionic polyelectrolyte solution for self-assembly and a single stabilization treatment to prepare a functional layer on the surface of the base film; A photothermal layer is deposited on the surface of the functional layer to obtain a composite film; The cationic polyelectrolyte solution includes an amphiphilic chitosan derivative solution.
5. The method for preparing the composite membrane as described in claim 4, characterized in that, The amphiphilic chitosan derivative solution contains 0.3% to 1% by mass of the amphiphilic chitosan derivative; and / or, The anionic polyelectrolyte solution includes a polyacrylic acid solution, wherein the mass percentage of polyacrylic acid in the polyacrylic acid solution is 0.05% to 0.2%.
6. The method for preparing the composite membrane as described in claim 4, characterized in that, The first stabilization treatment involves treating the self-assembled base film with a stabilizing solution, wherein: The stable solution comprises at least one of ethyltris(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide; and / or, The molar concentration of the stabilized solution is 1–50 mmol / L; and / or, The stabilization treatment time is 5 to 30 minutes.
7. The method for preparing the composite membrane as described in claim 4, characterized in that, The step of preparing a photothermal layer on the surface of the functional layer includes: The photothermal material is mixed with a dispersing solvent to obtain a photothermal material dispersion. The photothermal material dispersion is coated onto the surface of the functional layer at least twice, followed by a second stabilization treatment, to deposit a photothermal layer on the surface of the functional layer and obtain a composite film.
8. The method for preparing the composite membrane as described in claim 7, characterized in that, The dispersion solvent includes water and an organic solvent, the organic solvent including at least one of ethanol and isopropanol; and / or, The duration of the secondary stabilization treatment is 5-10 minutes; and / or, The mass of photothermal material in the dispersion of photothermal material in a single coating is 10~20μg per square centimeter.
9. The method for preparing the composite membrane as described in claim 4, characterized in that, The steps for preparing the base film include: The polyaryletherketone solution is mixed with additives to obtain a casting solution; The casting solution is coated into a film by a scraper, evaporated in an air section, and treated in a water bath to obtain a base film. The polyaryletherketone solution comprises polyaryletherketone and a solvent, wherein the polyaryletherketone has hydrophilic groups; in: The polyaryletherketone solution comprises polyaryletherketone and a solvent, the solvent comprising dimethylacetamide; and / or, The additive includes ethylene glycol monomethyl ether; and / or, In the casting solution, the additive accounts for 5% to 15% by mass; and / or, In the polyaryletherketone solution, the polyaryletherketone accounts for 14% to 20% by mass; and / or, The evaporation time of the air segment is 1~10s; and / or, The temperature of the water bath treatment is 22~28℃.
10. The application of a composite membrane as described in any one of claims 1 to 6 in a solar interface evaporation purification device, characterized in that, The solar-powered interface evaporation purification device is used for seawater desalination and / or the treatment of saline wastewater.
Citation Information
Patent Citations
Polymer microporous membrane as well as preparation method and application thereof
CN108889138A
Carbon material microbead / polymer composite film, and preparation method and applications thereof
CN110465208A
Carbon fiber-based solar photo-thermal efficient conversion material with excellent mechanical property as well as preparation method and application of carbon fiber-based solar photo-thermal efficient conversion material
CN116768309A
Photo-thermal material composition and application thereof, photo-thermal composite film and preparation method and application thereof
CN120005452A
Hydrophobic photothermal membranes, devices including the hydrophobic photothermal membranes, and methods for solar desalination
US20150353385A1